CHARACTERIZATION OF THE ARANG FORMATION SANDSTONE RESERVOIR IN THE âKMLâ FIELD, WEST NATUNA BASIN THROUGH A TRIGONOMETRIC APPROACH TO ATTRIBUTES OF CURVED PSEUDO ELASTIC IMPEDANCE (CPEI) AND PSEUDO DENSITY - Kamal
The “KML” field is a hydrocarbon field located in the West Natuna Basin. This study focuses on one of the formations in the West Natuna Basin, namely the Arang Formation. The lithology of this formation is clean sandstone and shally sandstone so that there is an alternation between sand and shale. Therefore, an elastic parameter is needed that is able to separate lithology and fluid in this field. The data used in this study are well data, seismic data (partial angle stack near, mid, far), and horizon data. Analysis of sensitive parameters shows that the Vp/Vs ratio and Mu-Rho parameters are sensitive to separate fluid and lithology. The Linear Programming Sparse Spike (LPSS) inversion method is used to produce the Vp/Vs ratio and Mu-Rho inversion. The Vp/Vs ratio inversion cross-section is obtained from the AI/SI inversion and the extended elastic impedance method. After comparison, the extended elastic impedance Vp/Vs ratio inversion results have a better correlation than the AI/SI results. Mu-Rho inversion cross section obtained from the extended elastic impedance method. The results of the Vp/Vs ratio inversion are used to describe the distribution of hydrocarbon fluids and the MuRho inversion is used to describe the distribution of lithology. The results of the EEI Vp/Vs ratio and Mu-Rho inversion are used to create the Curved Pseudo Elastic Impedance (CPEI) attribute with a trigonometric approach as a projection of the water saturation volume. Pseudo Density is created from a crossplot between ln AI and log density, then the results of Pseudo Density are used to create the porosity volume. The results of the study show that the CPEI and Pseudo Density attributes are able to describe the distribution of lithology and hydrocarbons. From the slicing results, it can be seen that the distribution of low water saturation and high porosity are in high areas.